Digital inclusion and assistant technologies: analysis of scientific production indexed in the Information Science Database (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
This research addresses accessibility, digital inclusion and assistive technologies and how they are fundamental to ensuring access to information. From this perspective, this research aims to analyze scientific production that addresses digital inclusion and assistive technologies indexed in the Information Science Database, from 2004 to 2024. Through an exploratory study with a quantitative approach, a bibliometric analysis was carried out which revealed a total of 939 publications on "digital inclusion" and 119 on "assistive technologies" throughout the period analyzed. This analysis highlights the frequency with which the terms are discussed, as well as the need for continuity in academic production to keep up with the demands of the digital society and ensure greater equity in access to information.
Keywords: digital inclusion; assistive technologies; bibliometric study